Ventilatory efficiency in cardiac amyloidosis—A systematic review and meta‐analysis - Robin Willixhofer; Elisabetta Salvioni; Nicolò Capra; Mauro Contini; Jeness Campodonico; Piergiuseppe Agostoni (Physiological Reports)
Abstract In cardiac amyloidosis (CA) cardiopulmonary exercise testing (CPET) is underexplored. This study evaluated exercise limitations in CA using CPET, focusing on the ventilation‐to‐carbon dioxide production (VE/VCO2) slope and peak oxygen uptake (VO2). Seventeen studies involving 1505 patients were analyzed and systematically reviewed according to PRISMA reporting guidelines. Subgroup analyses assessed differences by diagnosis (ATTR vs. AL), CPET modality, and age. The cohort included 12% with AL, 80% with ATTR (23% hereditary [ATTRv], 70% wild‐type [ATTRwt], 7% unspecified), and 8% unidentified subtypes. VE/VCO2 slope was elevated across ATTR subgroups: 38.4 (95% CI: 36.9–40.0, I2 = 57%) in ATTRwt and 37.9 (95% CI: 35.1–40.7, I2 = 70%) in ATTRv. ATTR patients were older than AL patients by 9.0 years (95% CI: 0.4–17.6, I2 = 88%) and had a higher VE/VCO2 slope: 2.5 (95% CI: 0.2–4.8, I2 = 0%). CPET modality influenced peak VO2, which was lowest for treadmill exercise (13.7, 95% CI: 12.7–14.8, I2 = 0%, mL/min/kg) compared to upright cycle ergometry (14.7, 95% CI: 14.3–15.1, I2 = 33%) and semi‐recumbent cycle ergometry (14.5, 95% CI: 14.1–14.9, I2 = 28%). A high VE/VCO2 slope characterizes both ATTRwt and ATTRv, while AL patients are younger with lower VE/VCO2 slope levels. Peak VO2 in ATTR patients may depend on exercise modality.